Problematika Nikah Misyar dalam Tinjauan Sosiologis dan Psikologis - Agung Tri Nugroho, M.Sy (Al Qadhi Journal of Islamic Family Law, 2019)
ABSTRACT In this study reveals various problems concerning Misyar Wedding (tamasya) which in its term is Marriage which in which the woman gets part of his rights which is arranged at the time of the marriage contract, such as not getting a place to live, livelihood and continuity to live with it. While in KHI 1974 According to Islamic Religion, Marriage is one of the forms of worship that the holiness needs to be maintained by both parties both husband and wife. And his marriage aims to form a happy, prosperous and everlasting family forever. Marriage requires maturity and physical and mental preparation because marriage / marriage is something sacred and can determine a person's way of life. If seen from the review of Psychology and sociology then there will be many polemics that arise from the rights and responsibilities of the husband in the living more specifically the child's future and psychological child, this issue should be Ministry of Religious institutions under the Government of Indonesia need strict supervision by the practice of marriage Misyar by applying regulation in the regions of Indonesia and the implications of the marriage.